Use of Abbreviations and Acronyms in Instagram Account @Aniesbaswedan - Luqman Muflihul Muniyf; Hilda Hilaliyah; Chadis Chadis (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study was to determine the number of abbreviations and acronyms used on the Instagram account @aniesbaswedan. The research method used is descriptive qualitative. The instrument used is in the form of an analytical table that is compiled based on the concepts of abbreviations and acronyms contained in Pedoman Umum Ejaan Bahasa Indonesia (PUEBI). The research technique used is content analysis technique. The data obtained is then classified according to the specified indicators. The results showed that the total findings were 98 findings consisting of abbreviations as many as 55 findings or 56% and acronyms 43 findings or 44% of the total 100%. The use of abbreviations is more widely used by admins than acronyms in informing the public.Keywords: Abbreviations, Acronyms, Instagram Accounts